Exploring a sustainable synthesis of artemisinin - Sharif, Nasiru (2022)
Malaria causes many deaths per year, according to report released by WHO in November 2020, there were 229 million cases of malaria in 2019, with estimated number of deaths which stood at 409, 000. With the children under the age of 5 years being the most vulnerable, accounting for 67 % (274 000) of all malaria death worldwide. The World Health Organization has recommended Artemisinin-based combination therapies (ACTs) for the treatment of uncomplicated malaria caused by the parasite P. falciparum.